Occurrence of mcr-1 and mcr-2 colistin resistance genes in porcine Escherichia coli isolates (2010–2020) and genomic characterization of mcr-2-positive E. coli - Ewers, Christa; Göpel, Lisa; Prenger-Berninghoff, Ellen; Semmler, Torsten; Kerner, Katharina; Bauerfeind, Rolf (Frontiers in microbiology, 2022)
The global emergence of plasmid-mediated colistin resistance is threatening the efficacy of colistin as one of the last treatment options against multi-drug resistant Gram-negative bacteria. To date, ten -genes ( to ) were reported. While has disseminated globally, the occurrence of was reported scarcely. We determined the occurrence of and genes among isolates from swine and performed detailed genomic characterization of -positive strains. In the years 2010-2017, 7,614 porcine isolates were obtained from fecal swine samples in Europe and isolates carrying at least one of the virulence associated genes predicting Shiga toxin producing (STEC), enterotoxigenic (ETEC) or enteropathogenic (EPEC) were stored. 793 (10.4%) of these isolates carried the gene. Of 1,477 additional isolates obtained from sheep blood agar containing 4 mg/L colistin between 2018 and 2020, 36 (2.4%) isolates were -positive. In contrast to , the gene occurred at a very low frequency (0.13%) among the overall 9,091 isolates. Most -positive isolates originated from Belgium ( = 9), one from Spain and two from Germany. They were obtained from six different farms and revealed multilocus sequence types ST10, ST29, ST93, ST100, ST3057 and ST5786. While the originally described was predominant, we also detected a new variant in two isolates from Belgium, which was termed . MCR-2 isolates were mostly classified as ETEC or ETEC-like, while one isolate from Spain represented an atypical enteropathogenic (aEPEC; +). The ST29-aEPEC isolate carried on the chromosome. Another eight isolates carried their gene on IncX4 plasmids that resembled the pKP37-BE MCR-2 plasmid originally described in Belgium in 2015. Three ST100 isolates from a single farm in Belgium carried the gene on a 47-kb self-transmissible IncP type plasmid of a new IncP-1 clade. This is the first report of genes in isolates from Germany. The detection of a new allele and a novel plasmid backbone suggests the presence of so far undetected variants and mobilizable vehicles.